2010
DOI: 10.1051/0004-6361/200913775
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical evolution of titanium, strontium, and yttrium spots on the surface of the HgMn star HD 11753

Abstract: Aims.We gathered about 100 high-resolution spectra of three typical HgMn (mercury-manganese) stars, HD 11753, HD 53244, and HD 221507, to search for slowly pulsating B-like pulsations and surface inhomogeneous distribution of various chemical elements.Methods. Classical frequency analysis methods were used to detect line profile variability and to determine the variation period. Doppler imaging reconstruction was performed to obtain abundance maps of chemical elements on the stellar surface. Results. For HD 11… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 29 publications
5
64
0
Order By: Relevance
“…The rotational period of ϕ Phe, 9. d 54 (Briquet et al 2010), was recently revised to 9. d 531 (Korhonen et al 2011). This improvement corresponds to a negligible change of the rotational phases of our observations.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rotational period of ϕ Phe, 9. d 54 (Briquet et al 2010), was recently revised to 9. d 531 (Korhonen et al 2011). This improvement corresponds to a negligible change of the rotational phases of our observations.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Surface maps were reconstructed using the Doppler imaging code INVERS10 . Unlike the previous attempt to study chemical spots in ϕ Phe (Briquet et al 2010), our analysis is based on simultaneous modelling of multiple spectral lines, which significantly improves reliability of the DI maps. The maps of Y were reconstructed from nine spectral lines, Sr from three, Ti from nine, and Cr from eight spectral lines.…”
Section: Doppler Imagingmentioning
confidence: 99%
“…However, some binary HgMn stars have been shown to display spectroscopic variations (Adelman et al 2002;Kochukhov et al 2005;Hubrig et al 2006a;Briquet et al 2010). The non-uniform surface abundances invoked to explain these variations appear to evolve with time (Kochukhov et al 2007).…”
Section: Hgmn Starsmentioning
confidence: 99%
“…A patchy surface distribution of some chemical species has first been firmly established from the detection of large, daily changes in the strength of Hg ii λ3984 in the primary component of α And (Adelman et al 2002), but has also been subsequently found in other HgMn stars (e.g., Kochukhov et al 2005;Briquet et al 2010;Hubrig et al 2011). To date, Doppler imaging techniques have been used to infer the distribution (and evolution) of chemical spots in four B stars with HgMn peculiarity: AR Aur A A35, page 11 of 14 A&A 561, A35 (2014) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among the processes invoked by these authors to explain these observations, they considered the time-dependent atomic diffusion scenario proposed by Alecian (1998). Line-profile variations have been detected during the last decade in several HgMn stars and interpreted in terms of abundance spots in the photosphere (e.g., Adelman et al 2002;Kochukhov et al 2005;Hubrig et al 2006;Briquet et al 2010). These kinds of patches generally concern elements that have low abundances in normal stars (Sr, Y, Pt, Zr, and Hg) and which are suspected of being concentrated in high-altitude (above log τ = -4) clouds.…”
Section: Introductionmentioning
confidence: 99%